American samurai : - Lareau, William (Warner Books, 1991)
The American samurai knows that the old attitudes just won't cut it in today's market. He knows that the battle to make the U.S. a great economic power might be lost, but he's still willing to fight to the end to put quality back in American products. If you are ready to become a crusader for quality and success, William Lareau shows you how. In frank language, he explains: Why managers -- not workers -- are responsible for 99% of all day-to-day business breakdowns, Why every American samurai must learn the Japanese word "Kaizen" -- and put it into effect in their company today